2022
DOI: 10.3390/su14095614
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hydraulic Fracturing in Stimulation of the Oil and Gas Wells in Romania

Abstract: This paper presents the application of the hydraulic fracturing method in Romania, exemplified by three case studies. In the current conditions in which the oil and gas prices have risen above the limit of affordability, Romania, one of the few producers in Europe, is trying to solve the problems that have arisen through various methods, which are as follows: offshore drilling, gas underground storage, field rehabilitation and increasing the efficiency of applied technologies. The application of hydraulic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Zhao et al 8 conducted research on the seepage behavior of fracture networks after hydraulic fracturing of shale and concluded that the seepage channels formed during the process can significantly enhance the permeability of shale. In addition, hydraulic fracturing is also used in the commercial development of oil and gas wells to increase production 9–11 . These findings demonstrate that hydraulic fracturing has a substantial impact on rock permeability.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Zhao et al 8 conducted research on the seepage behavior of fracture networks after hydraulic fracturing of shale and concluded that the seepage channels formed during the process can significantly enhance the permeability of shale. In addition, hydraulic fracturing is also used in the commercial development of oil and gas wells to increase production 9–11 . These findings demonstrate that hydraulic fracturing has a substantial impact on rock permeability.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, hydraulic fracturing is also used in the commercial development of oil and gas wells to increase production. [9][10][11] These findings demonstrate that hydraulic fracturing has a substantial impact on rock permeability.…”
mentioning
confidence: 97%
“…Challenges such as the low injection capacity of water injection wells and difficulty in well productivity enhancement have emerged. Hydraulic fracturing technology is one of the key methods of increasing production [5][6][7][8][9][10]. Fracturing fluid plays an important role in fracturing, and its performance directly affects the effectiveness of the transformation.…”
Section: Introductionmentioning
confidence: 99%